The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10633-007-9076-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically defined components of the normal porcine multifocal ERG

Abstract: Multifocal electroretinograms (mfERG) from isoflurane anesthetized pigs were recorded and sequential application of TTX, NMDA, APB and PDA were used to identify contributions to the mfERG from inner retinal neurons, ON-pathway, OFF-pathway and photoreceptors. The cellular origins of the first-order kernel (K1) and the first slice of the second-order kernel (K2.1) porcine mfERG are contributed from both inner and outer retina. For the K1 waveform, the n1 involved responses of cone photoreceptors and OFF-bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 30 publications
4
59
0
Order By: Relevance
“…Assuming that the minimum vitreous concentration of ISO approximates its clinical MBC, 25 ll ISO in intra-vitreal injection would be double the minimum amount of ISO required. The concentrations of pharmacological agents, besides ISO and propofol, were evidently sufficient in previous experiments in other animals [18,19] and in pig [3,4,20] In our experiments, all these effects on the flash ERG were verified. NMDA is an ionotropic glutamateric receptor agonist that depolarizes cells with NMDA receptors (NMDAr), such as ganglion cells and amacrine cells.…”
Section: Drug Administrationsupporting
confidence: 79%
See 1 more Smart Citation
“…Assuming that the minimum vitreous concentration of ISO approximates its clinical MBC, 25 ll ISO in intra-vitreal injection would be double the minimum amount of ISO required. The concentrations of pharmacological agents, besides ISO and propofol, were evidently sufficient in previous experiments in other animals [18,19] and in pig [3,4,20] In our experiments, all these effects on the flash ERG were verified. NMDA is an ionotropic glutamateric receptor agonist that depolarizes cells with NMDA receptors (NMDAr), such as ganglion cells and amacrine cells.…”
Section: Drug Administrationsupporting
confidence: 79%
“…Multifocal electroretinogram (mfERG) recordings obtained from anesthetized primates [1,2] and pig [3,4] have been measured before and after the injection of pharmacological agents with known effects in blocking the activities of specific neural circuits. These findings have been used to define the contributions of specific in vivo retinal pathways to the mfERG response.…”
Section: Introductionmentioning
confidence: 99%
“…P1 is of photoreceptor and bipolar cell origin [55,56] and is a good representative of outer retinal function. For ICG, the N1 amplitude was significantly smaller in injected eyes than in healthy fellow eyes (p00.023), and for BBG this was the case for N2 (p00.008), but the significance of these findings is unclear; N1 is probably of photoreceptor origin, and N2 is of unknown origin [55].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the middle and inner retinal activity contributed signifi cantly to the shaping of the mfERGs in rabbits, as in other animals such as monkeys, pigs, and cats. 11,24,25 Responses from the visual streak were successfully identifi ed by their higher amplitudes as reported, 20 After elimination of the neural activity of the middle retinal neurons by an intravitreal injection of APB and PDA, the cone responses were obtained. We found that the amplitude of the negative defl ection of the WT rabbits did not differ signifi cantly from that of the Tg rabbits, whereas Kondo et al 6 showed that the full-fi eld cone a-wave amplitudes elicited by strong stimuli were signifi cantly smaller in Tg than WT rabbits at 12 weeks of age.…”
Section: Discussionmentioning
confidence: 87%